ANALISIS PERENCANAAN DAN PENGENDALIAN CADANGAN PIUTANG RAGU-RAGU PADA PT. KIMIA FARMA TRADING & DISTRIBUTION CABANG SEMARANG - Desi Ariyati; Rodhiyah Rodhiyah; Andi Wijayanto (Jurnal Ilmu Administrasi Bisnis, 2014)
Credit sales have not all risks can be realized receivable into cash so that the company established a reserve for doubtful accounts receivable which aims to have a significant portion of total assets to reflect the liquidity and credit sales results are still in the form of accounts receivable to reflect profitability. PT. Kimia Farma Trading & Distribution Branch Semarang have in shaping policy reserves for doubtful accounts but these policies have not been able to reflect liquidity and profitability as reserves for doubtful accounts has a value greater than doubtful accounts. The purpose of the study was to determine the liquidity and profitability by implementing Markov Chain Analysis. he method used is descriptive analytical fact finding Markov Chain Analysis of the calculation results are considered to reflect the liquidity and profitability. The results of the study are reserve for doubtful accounts of 2.5% - 3.5%. determined through the analysis of a Markov chain has a value smaller than the percentage of reserves for doubtful accounts is determined by the company so that the percentage Liquidity Current Ratio and Quick Ratio increased by 2% - 4%, Profitability is in addition to the percentage of ROA and net profit margin also increased by 1% - 2%. Companies can apply Markov chain analysis as an alternative policy determination of reserves for doubtful accounts.